Results and complications in elderly patients with acetabular fractures. Issue 4 (July 2016) - Scarcella, Nicholas; Schnaser, Erik; Vallier, Heather A.
Abstract : Background: The frequency of acetabular fractures in elderly patients is rising over time. The group presents with underlying challenges including osteoporosis, medical comorbidities, and varying levels of baseline physical and cognitive function. The purposes of this study were to characterize such patients and to determine rates of complications and secondary operations. We propose to identify injury and treatment features associated with optimal recovery. Methods: One hundred and ninety-three patients over the age of 60 with acute acetabular fractures were retrospectively reviewed over 12 yr. Complications, mortality, and secondary operations were documented for 171 patients with complete records and mean 18.5 mo follow-up. Ninety-one were treated operatively. Results: Patients who underwent open reduction and internal fixation had a mean age of 73 yr (vs. 69 yr, P =0.0003) and mean Injury Severity Score of 28.4 (vs. 15.7, P =0.001), consistent with higher-energy injuries and unstable fracture patterns compared to patients treated nonoperatively. Twenty-two percent developed early complications, with a trend toward a higher rate in patients treated surgically (27% compared to 16%, P =0.057). After open reduction and internal fixation, posttraumatic arthrosis and conversion to total hip arthroplasty occurred in 18% and 14%, respectively, compared to 3.8% of patients who had nonoperative care (both P <0.02). Mortality at 1 yr was 9.9% and at 5 yr was 29.5%, increasing with greater age. Conclusions: Additional research into efforts to expedite open reduction and internal fixation in stable patients with unstable fracture patterns may minimize complications by promoting mobility from bed. Further study to define patients better suited for nonoperative management is needed, as is investigation into the role of acute total hip arthroplasty or minimally invasive methods of reduction and fixation.